2021
DOI: 10.1152/jn.00098.2021
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of unilateral- versus bilateral-onset spike-wave discharges to ethosuximide and carbamazepine in the fluid percussion injury rat model of traumatic brain injury

Abstract: Unilateral-onset spike-wave discharges (SWDs) following fluid percussion injury (FPI) in rats have been used for nearly two decades as a model for complex partial seizures in human post-traumatic epilepsy (PTE). This study determined if SWDs with a unilateral versus bilateral cortical onset differed. In this experiment, 2-month old rats received severe FPI (3 atm) or sham surgery, and were instrumented for chronic video-electrocorticography (ECoG) recording (up to 9 months). The anti-seizure drug, carbamazepin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…These seizures were poorly responsive to subchronic treatment with carbamazepine, valproate, and carisbamate [147,148] but were prevented by mild focal cooling and brivaracetam [149,150]. However, the definition of focal seizures used by D'Ambrosio et al and their use for drug testing has been criticized [151][152][153], although the principal findings of D'Ambrosio were reproduced more recently by another group [154]. Furthermore, by increasing the severity of lateral FPI-induced brain injury, Smith et al [155] reported that >60% of rats exhibit convulsive SRSs within 2-5 weeks after FPI, which would make the model more suitable for drug testing, provided these findings can be replicated by other groups.…”
Section: Animal Models With Spontaneous Seizures That Are Resistant T...mentioning
confidence: 99%
“…These seizures were poorly responsive to subchronic treatment with carbamazepine, valproate, and carisbamate [147,148] but were prevented by mild focal cooling and brivaracetam [149,150]. However, the definition of focal seizures used by D'Ambrosio et al and their use for drug testing has been criticized [151][152][153], although the principal findings of D'Ambrosio were reproduced more recently by another group [154]. Furthermore, by increasing the severity of lateral FPI-induced brain injury, Smith et al [155] reported that >60% of rats exhibit convulsive SRSs within 2-5 weeks after FPI, which would make the model more suitable for drug testing, provided these findings can be replicated by other groups.…”
Section: Animal Models With Spontaneous Seizures That Are Resistant T...mentioning
confidence: 99%
“…These results suggest that SWDs are completely abolished after bilateral removal of the focal region, most likely by interfering with an intracortical columnar circuit ( 27 ), which also supports the cortical focus, whereas only inhibition of the local cortical network removed all seizures. Another unilateral onset is that SWDs have induced fluid percussion injury in rats, and it serves as a model for complex partial seizures in human post-traumatic epilepsy ( 28 ). In this model, anti-absence ethosuximide has been shown to suppress both unilateral or bilateral SWDs, whereas carbamazepine had no effect ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another unilateral onset is that SWDs have induced fluid percussion injury in rats, and it serves as a model for complex partial seizures in human post-traumatic epilepsy ( 28 ). In this model, anti-absence ethosuximide has been shown to suppress both unilateral or bilateral SWDs, whereas carbamazepine had no effect ( 28 ). Some drugs, such as potassium chloride, block SWDs somewhat in the ipsilateral cortex and thalamus ( 29 ).…”
Section: Discussionmentioning
confidence: 99%